2013
DOI: 10.2478/raon-2013-0041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety and analgesic consumption in patients with advanced cancer treated with zoledronic acid

Abstract: BackgroundThe aim of the study was evaluation of zoledronic acid with regard to safety, effect on analgesic consumption and impact on occurrence of skeletal related events in patients with bone lesions from solid tumors and multiple myeloma.MethodsWe conducted an observational, 12-month, phase IV and multi-center study. One hundred and twenty-five symptomatic (pain) bone-metastatic patients were included between 2007 and 2009: 92 prostate cancers, 28 multiple myelomas, 5 others. They were prescribed monthly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The biological film of VSD can separate the grafted wound from the outside [13,24]. Moreover, continuous negative pressure draining efficiently clears wound exudation in all directions and alters the environment for bacterial growth, leading to effectively preventing bacterial infection because these fluids act as media for bacteria growth and obstacles for capillary growth [21,25]. Above all, we referred that NPWT could lower the infection rate of the microskin transplanted wound in the first several days after skin autografts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The biological film of VSD can separate the grafted wound from the outside [13,24]. Moreover, continuous negative pressure draining efficiently clears wound exudation in all directions and alters the environment for bacterial growth, leading to effectively preventing bacterial infection because these fluids act as media for bacteria growth and obstacles for capillary growth [21,25]. Above all, we referred that NPWT could lower the infection rate of the microskin transplanted wound in the first several days after skin autografts.…”
Section: Discussionmentioning
confidence: 97%
“…The visual analog scale (VAS) is widely used in measuring local pain. The patient was asked to indicate his/her perceived pain intensity (most commonly) along a 100-mm horizontal line, and this rating was then measured as the VAS score [20,21].…”
Section: Clinical Criteriamentioning
confidence: 99%
“…Bisphosphonates are generally well tolerated, although they are occasionally associated with adverse events namely hypocalcemia, nephrotoxicity, pancytopenia and osteonecrosis [ 5 - 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…All bisphosphonates can cause hypocalcemia, regardless of their method of administration, although this is infrequently found to be a clinically symptomatic problem [ 7 , 8 ]. Of note, symptomatic hypocalcemia after ZA is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…A 12-month observational study of 125 patients with bone metastases (including 92 patients with prostate cancer) who were receiving zoledronic acid showed that hypocalcaemia of any grade occurred in 18.5% of the patients with prostate cancer. Of patients with any tumour type, hypocalcaemia of grade 3 or 4 occurred in 4% [ 31 ]. The higher incidence of hypocalcaemia encountered in real-world studies compared with clinical trials may reflect poor adherence to guidelines for calcium supplementation and monitoring of patients in clinical practice [ 12 ].…”
Section: Main Textmentioning
confidence: 99%